Nijmegen breakage Syndrome - how much do we know about this rare condition of Slavs? - disease overview - Adrianna Muciek; Martyna Mocarska; Anna Orłowska; Katarzyna Strakowska; Laura Opalska; Anna Maryńczak; Jan Mencel; Nicole Nitschke (Quality in Sport)
Nijmegen breakage syndrome (NBS) is a rare autosomal recessive defect of immunity, characterised by chromosomal instability and radiation sensitivity with a high predisposition to malignancy. The clinical manifestations of this condition include microcephaly, combined immunodeficiency, growth retardation and a range of additional abnormalities, including facial, skeletal and skin anomalies (such as café au lait spots and vitiligo). It is estimated that 40% of patients will develop cancer before reaching the age of 21 years. [1-2]